2014
DOI: 10.1039/c3ra48068b
|View full text |Cite
|
Sign up to set email alerts
|

Physico-mechanical and electrochemical corrosion behavior of soy alkyd/Fe3O4nanocomposite coatings

Abstract: Anticorrosive nanocomposite coatings were synthesized using soya alkyd a renewable polymer matrix and Fe3O4 nanoparticles as filler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 56 publications
3
63
0
Order By: Relevance
“…In addition, the incorporation of Fe 3 O 4 nanoparticles into polymer matrix may effectively improve some performances, such as the physic-mechanical and anticorrosive properties, which is owing to their M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT a certain mechanical properties and corrosion properties like other transition metal oxides (TiO 2 , ZrO 2 , NiO) possessing corrosion resistance inherently [17,18]. However, undecorated Fe 3 O 4 nanoparticles are easily tend to agglomerate due to its magnetic properties, thus leading to restrict their wide applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the incorporation of Fe 3 O 4 nanoparticles into polymer matrix may effectively improve some performances, such as the physic-mechanical and anticorrosive properties, which is owing to their M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT a certain mechanical properties and corrosion properties like other transition metal oxides (TiO 2 , ZrO 2 , NiO) possessing corrosion resistance inherently [17,18]. However, undecorated Fe 3 O 4 nanoparticles are easily tend to agglomerate due to its magnetic properties, thus leading to restrict their wide applications.…”
Section: Introductionmentioning
confidence: 99%
“…Also, hematite (Fe 2 O 3 ) NPs are proven to be useful nano-pigment which enhances mechanical and UV blocking properties [32] and corrosion resistance [32,33] of alkydbased waterborne coatings. The presence of nanoferrite (Fe 3 O 4 ) in soy alkyd coating improved thermal stability, physico-mechanical properties and corrosion resistance [34]. The addition of aluminum oxide (Al 2 O 3 ) nano-sized pigment into the alkyd coatings improved its corrosion [35,36] and UV resistance and mechanical properties, without altering the optical clarity of the prepared coating [36].…”
mentioning
confidence: 99%
“…The influence of different nano-sized pigments on the properties of alkyd-based NCs was extensively investigated in the literature [26][27][28][29][30][31][32][33][34][35][36][37]. It has been shown that application of zinc oxide (ZnO) as nanosized pigment improves mechanical and thermal properties [26] and corrosion resistance [27] of alkydbased coatings.…”
mentioning
confidence: 99%
“…Furthermore, the physico-mechanical and electrochemical corrosion behavior of the presence of different concentrations of Fe 3 O 4 in butylated melamine formaldehyde-cured soy alkyd was discussed. [16,17] Magnetic Fe 3 O 4 nanoparticles can improve the physicomechanical performance and the anticorrosion performance of epoxy resin because of their mechanical properties and corrosion properties. [16] However, naked Fe 3 O 4 nanoparticles can easily agglomerate, thus leading to restriction of its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Magnetic Fe 3 O 4 nanoparticles can improve the physicomechanical performance and the anticorrosion performance of epoxy resin because of their mechanical properties and corrosion properties. [16] However, naked Fe 3 O 4 nanoparticles can easily agglomerate, thus leading to restriction of its wide application. Based on the aforementioned reasons, the surfaces of the magnetic nanoparticles have been modified with specific ligands to give them good dispersibility and chemical stability.…”
Section: Introductionmentioning
confidence: 99%